THE EXPERIENCE OF ENHANCED EXTERNAL COUNTERPULSATION USING HARDWARE AND SOFTWARE COMPLEX “CARDIOPULSAR” IN PATIENTS WITH WIDESPREAD ATHEROSCLEROSIS OF VARIOUS LOCATION - I. M. Kuzmina; A. M. Shklyarov; E. V. Migunova (Неотложная медицинская помощь, 2017)
The article describes the experience of using enhanced external counterpulsation as one of circulatory support methods. Main indications for the procedure of non-invasive counterpulsation are briefly discussed. The characteristics of the hardware-software complex “Cardiopulsar” and methodological aspects of the procedure are highlighted. Clinical examples show the possibilities of the program counterpulsation in patients with coronary artery diseases and in patients with chronic diseases of lower limb arteries. We also report observation results of two patients who underwent treatment by EECP showing promising possibilities of counterpulsation in patients with multifocal atherosclerosis.